ECOLOGICAL CONSEQUENCES REDUCTION FROM AVIATION ACCIDENTS IMPACTS - N. I. Nikolaykin; E. Yu. Starkov (Научный вестник МГТУ ГА, 2016)
Aviation events as a source of emergency volley impact on the environment have been offered for consideration in the article. The classification of the emerging pollution types and the analysis of the problems that arise when combustivelubricating materials spill at the place of airplane crash are presented in the article.The system of measures aimed at reducing negative ecological impact on the soil of the affected territories through its detoxification has been offered. Carbon sorbents application has been proved. The dependences for calculating the necessary amount of active coals have been recommended. The proposed sequence of works to be carried out on the polluted territory has been shown.